PAPÉIS SOCIAIS DOS TUTORES EM CURSOS DE LICENCIATURA EAD: UM ESTUDO SOBRE AS REPRESENTAÇÕES SOCIAIS - Pasqualini, Adriana Regina Borges (2010)
This paper aimed to investigate the social representations that tutors have about their own performance in distance teaching degree courses. With the purpose of analyzing if the tutors recognize themselves as teachers who participate in the students education process, the field study had as subjects tutors who graduated in teaching and act in courses at the same level in this modality in a Private Institution of Higher Education in the Greater São Paulo area. The routes followed in this investigation are justified by the personal formative trajectory and by the experience spaces that are built in the everyday practice of this activity. A study on the available models of Higher Education distance learning in Brazil, a brief historical review about DL aspects in this country, an explanation about the model in which these tutors act and an approximation to the teaching profession Social Representations are approaches presented in this paper. With this work, we intended to contribute to education by improving the knowledge about the tutor who is responsible for assisting students in the virtual learning environment, considering the possibilities of expansion and democratization of education in the country. The results reveal that tutors tend to consider their occupation as one that is confounded with the essence of teaching professionality, an indication that shows the necessity of a deeper reflexion on these professionals function and actuation.(AU)